Tolerogenic Immunotherapy: Targeting DC Surface Receptors to Induce Antigen-Specific Tolerance - Castenmiller, Charlotte; Keumatio-Doungtsop, Brigitte-Carole; van Ree, Ronald; de Jong, Esther C.; van Kooyk, Yvette (Frontiers in Immunology, 2021)
Dendritic cells (DCs) are well established as major players in the regulation of immune responses. They either induce inflammatory or tolerogenic responses, depending on the DC-subtype and stimuli they receive from the local environment. This dual capacity of DCs has raised therapeutic interest for their use to modify immune-activation via the generation of tolerogenic DCs (tolDCs). Several compounds such as vitamin D3, retinoic acid, dexamethasone, or IL-10 and TGF-β have shown potency in the induction of tolDCs. However, an increasing interest exists in defining tolerance inducing receptors on DCs for new targeting strategies aimed to develop tolerance inducing immunotherapies, on which we focus particular in this review. Ligation of specific cell surface molecules on DCs can result in antigen presentation to T cells in the presence of inhibitory costimulatory molecules and tolerogenic cytokines, giving rise to regulatory T cells. The combination of factors such as antigen structure and conformation, delivery method, and receptor specificity is of paramount importance. During the last decades, research provided many tools that can specifically target various receptors on DCs to induce a tolerogenic phenotype. Based on advances in the knowledge of pathogen recognition receptor expression profiles in human DC subsets, the most promising cell surface receptors that are currently being explored as possible targets for the induction of tolerance in DCs will be discussed. We also review the different strategies that are being tested to target DC receptors such as antigen-carbohydrate conjugates, antibody-antigen fusion proteins and antigen-adjuvant conjugates.